FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN KUNJUNGANULANG PASIEN HIPERTENSI STADIUM II DI PUSKESMAS NGOMBOL KABUPATEN PURWOREJO - E Ernawati; Radina Kolasari (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Non-compliance in on the treatment programs is a major problem of patients with hypertension. Success in controlling high blood pressure is a joint effort between the patient and the doctor in charge. Compliance of a patient suffering from hypertension can not simply be based on compliance in taking antihypertensive drugs but also it requires the active role of patients and willingness to check their health to the doctor according to a specified schedule and recommended lifestyle changes. Some factors influencing the compliance of hypertensive patients that affect complience among hypertensive patients re-visit are age, education, economy, knowledge, and attitude.The aim of this study is to determine the factors influencing the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center Purworejo.This study used an analytical method with cross sectional correlation. Analysis of data used frequency distributions and bivariate analysis using chi square statistic test followed by logistic regression analysis.Age factor influenced the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center with p: 0.102. Education influenced the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center with p: 0.010. Knowledge influenced the influencing the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center with p: 0.000. Attitudes influenced the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center with p: 0.000. Attitudes about hypertension is the most dominant factor influencing the compliance of stadium II hypertensive patients to re-visit Ngombol Community Health Center p: 0.034. Keywords: age, education, economy, knowledge, attitude, complience to re-visit, hypertensive patients